Rehydration Process in Rustyback Fern (Asplenium ceterach L.): Profiling of Volatile Organic Compounds - Suzana Živković; Marijana Skorić; Mihailo Ristić; Biljana Filipović; Milica Milutinović; Mirjana Perišić; Nevena Puač (Biology, 2021)
When exposed to stressful conditions, plants produce numerous volatile organic compounds (VOCs) that have different biological and environmental functions. VOCs emitted during the rehydration process by the fronds of desiccation tolerant fern Asplenium ceterach L. were investigated. Headspace GC–MS analysis revealed that the volatiles profile of rustyback fern is mainly composed of fatty acid derivatives: isomeric heptadienals (over 25%) and decadienals (over 20%), other linear aldehydes, alcohols, and related compounds. Aerial parts of the rustyback fern do not contain monoterpene-type, sesquiterpene-type, and diterpene-type hydrocarbons or corresponding terpenoids. Online detection of VOCs using proton-transfer reaction mass spectrometry (PTR–MS) showed a significant increase in emission intensity of dominant volatiles during the first hours of the rehydration process. Twelve hours after re-watering, emission of detected volatiles had returned to the basal levels that corresponded to hydrated plants. During the early phase of rehydration malondialdehyde (MDA) content in fronds, as an indicator of membrane damage, decreased rapidly which implies that lipoxygenase activity is not stimulated during the recovery process of rustyback fern.